EVALUASI PENGARUH PUPUK KANDANG AYAM DAN NPKMg TERHADAP PRODUKTIVITAS TANAMAN AREN (Arenga pinnata Merr.) - Herawati, Netti; Ardi, Ardi; Silvia, Silvia Permata Sari; Devinda, Devinda (Fakultas Pertanian Universitas Janabadra, 2025)
Sugar palm (Arenga pinnata Merr.) is a plantation commodity that is very beneficial ecologically and financially because it can adapt to various geographical conditions such as mountains, valleys, riverbanks, and undulating land. However, the development of this plant is still constrained by low cultivation intensification, unstructured planting patterns, and optimal land use, resulting in low productivity. Increasing the productivity of sugar palm plants can be achieved through intensive cultivation. The purpose of this study was to study how chicken manure and NPKMg fertilizer affect the growth of sugar palm plants and determine the best fertilizer dosage. The study was conducted in February-May at the experimental garden of the Faculty of Agriculture, Andalas University at an altitude of ±250 meters above sea level. The method used was a 4x3 factorial Randomized Block Design (RAK), consisting of three replications with a total of 36 experimental units. The first factor was the dose of chicken manure (5 kg, 10 kg, 15 kg, and 20 kg) and the second factor was the dose of NPKMg fertilizer (20 g, 30 g, and 40 g). The data were analyzed using the F test at the 5% level, followed by the DNMRT test. The results showed that there was no significant relationship between the provision of chicken manure and NPKMg fertilizer on the growth of sugar palm plants. In addition, both types of fertilizers did not have a significant impact on plant growth, so the optimal dose could not be determined.